2001
DOI: 10.1002/cne.10094
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circular muscle motor neurons of the duodenum and distal colon in the Australian brush‐tailed possum

Abstract: The motor innervation of the duodenum and distal colon remains uncharacterized within the same species. Our aim was to compare the projections and neurochemical properties of duodenal and distal colon circular muscle motor neurons. Circular muscle motor neurons were retrogradely traced by using a neural tracer in vitro, processed for choline acetyltransferase (ChAT) and nitric oxide synthase (NOS) immunoreactivity and then visualized by using indirect immunofluorescence. A mean of 372 +/- 64 and 156 +/- 23 neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…As to the co‐expression of nNOS‐ and ChAT‐IR, our results (about 86%) are not consistent with those obtained in the guinea pig (Li and Furness, ), pig (Brehmer et al., ) or human (Beck et al., ) where only a small percentage (16% in the guinea pig, less than 2% in the pig and about 3% in the human) of nNOS‐IR MP co‐expressed ChAT‐IR. The mixed phenotype (ChAT‐ and nNOS‐IR) seems a feature of MP interneurones, although functional data obtained on Australian brush‐tailed possum demonstrated that the mixed phenotype (NOS + /ChAT + ) might be a feature of CML myenteric motor neurones (Konomi et al., ). Furthermore, it was shown that nitric oxide can modulate cholinergic transmission in canine colon muscle strips (Rae et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…As to the co‐expression of nNOS‐ and ChAT‐IR, our results (about 86%) are not consistent with those obtained in the guinea pig (Li and Furness, ), pig (Brehmer et al., ) or human (Beck et al., ) where only a small percentage (16% in the guinea pig, less than 2% in the pig and about 3% in the human) of nNOS‐IR MP co‐expressed ChAT‐IR. The mixed phenotype (ChAT‐ and nNOS‐IR) seems a feature of MP interneurones, although functional data obtained on Australian brush‐tailed possum demonstrated that the mixed phenotype (NOS + /ChAT + ) might be a feature of CML myenteric motor neurones (Konomi et al., ). Furthermore, it was shown that nitric oxide can modulate cholinergic transmission in canine colon muscle strips (Rae et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Motor neurons of the entire gastrointestinal tract contain acetylcholinetransferase ( Ratcliffe et al , 1998 ; Konomi et al , 2002 ; Porter et al , 2002 ) and the tachykinins such as substance P (SP), neurokinin A (NKA) and B (NKB) ( Sandler et al , 1991 ; Shuttleworth et al , 1991 ; Yunker et al , 1999 ; Yip et al , 2003 ). ACh is the main excitatory neurotransmitter in the gastrointestinal tract but tachykinins can also play an important role in specific gastrointestinal regions ( Cao et al , 2000 ; Krysiak and Preiksaitis, 2001 ; El‐Mahmoudy et al , 2003 ).…”
Section: Excitatory Neurotransmitters In the Losmentioning
confidence: 99%
“…11 Neurally released VIP and NO is proposed to regulate fluid transport by the gall bladder epithelium under some pathological conditions. 11,15,17,18 The technique of retrograde tracing in vitro, combined with immunohistochemistry has been used to characterize the projections and neurochemical code of enteric neurones within the intestine and stomach of several laboratory species [19][20][21][22] and humans. 23,24 More recently, we applied these techniques to elucidate the motor innervation of the gall bladder in the Australian Brush-tailed possum.…”
Section: Introductionmentioning
confidence: 99%